One-Year Functional, Cognitive, and Psychological Outcomes Following the Use of Extracorporeal Membrane Oxygenation in Coronavirus Disease 2019: A Prospective Study. (10th September 2021) - Rajajee, Venkatakrishna; Fung, Christopher Mon-Chee; Seagly, Katharine Surella; Park, Pauline Kyonsook; Raghavendran, Krishnan; Machado-Aranda, David Antonio; Scott, Jonathan William; Delano, Matthew Joseph; Abou El Ela, Ashraf Shaaban Abdel Aziz; Haft, Jonathan William; Williamson, Craig Andrew; McSparron, Jakob Israel; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: To prospectively describe 1-year outcomes, with a focus on functional outcome, cognitive outcome, and the burden of anxiety, depression, and post-traumatic stress disorder, in coronavirus disease 2019 patients managed with extracorporeal membrane oxygenation. Design: Prospective case series. Setting: Tertiary extracorporeal membrane oxygenation center in the United States. Patients: Adult coronavirus disease 2019 acute respiratory distress syndrome patients managed with extracorporeal membrane oxygenation March 1, 2020, to July 31, 2020. Interventions: Baseline variables, treatment measures, and short-term outcomes were obtained from the medical record. Survivors were interviewed by telephone, a year following the index intensive care admission. Functional outcome was assessed using the modified Rankin Scale and the World Health Organization Disability Assessment Scale 2.0. Cognitive status was assessed with the 5-minute Montreal Cognitive Assessment. The Hospital Anxiety and Depression Scale was used to screen for anxiety and depression. Screening for post-traumatic stress disorder was performed with the Posttraumatic Stress Disorder Checklist 5 instrument. Measurements and Main Results: Twenty-three patients were managed with extracorporeal membrane oxygenation, 14 (61%) survived to hospital discharge. Thirteen (57%) were alive at 1 year. One patient was dependent on mechanical ventilation, another intermittently required supplemental oxygen at 1 year. The median modified Rankin Scale score was 2 (interquartile range, 1–2), median World Health Organization Disability Assessment Scale 2.0 impairment score was 21% (interquartile range, 6–42%). Six of 12 previously employed individuals (50%) had returned to work, and 10 of 12 (83%) were entirely independent in activities of daily living. The median Montreal Cognitive Assessment score was 14 (interquartile range, 13–14). Of 10 patients assessed with Hospital Anxiety and Depression Scale, 4 (40%) screened positive for depression and 6 (60%) for anxiety. Four of 10 (40%) screened positive for post-traumatic stress disorder. Conclusions: Functional impairment was common a year following the use of extracorporeal membrane oxygenation in coronavirus disease 2019, although the majority achieved independence in daily living and about half returned to work. Long-term anxiety, depression, and post-traumatic stress disorder were common, but cognitive impairment was not.